In silico design in designing xylanase for biobleaching industry - Noorbatcha, Ibrahim Ali; Abdul Hadi, Muaz; Ismail, Ahmad Faris; Mohd. Salleh, Hamzah (Asian Network for Scientific Information, 2009)
The use of hemicellulolytic enzymes has recently attracted considerable interest as a substitute for chlorine chemicals in pulp bleaching. The challenges in incorporating enzyme to the bleaching system are to have a stable and active xylanase at high temperatures and higher alkaline pH conditions. In this study, we have used computational methods to analyze the structural factors responsible for the activity and themostability of Bacillus circulans xylanase which have been identified as one of the promising xylanase source to treat the pulp before bleaching it through the conventional bleaching sequences. Simulated point mutation shows that arginine substitution potentially increased the number of hydrogen bond; correlate with the xylanase activity and some changes in amino acid sequence specifically to the α-helix and β-sheet appeared to be promising in improving thermostability of xylanase. This in silico method results can be used to develop new efficient xylanase for pulp bleaching industry.